Linear relationship of a soil total water potential function and relative yield—A technique to control salinity and water stress on golf courses and other irrigated fields - Beltrão, José (2021)
A simple empirical approach is proposed for the determination of crop relative yield (%) through the soil total water potential (kPa). Recurring to decimal logarithms, from analytical exponential expressions, a linear simple relationship of soil total water potential Ψt (matric Ψm + potential Ψo) function and crop relative yield was studied and developed. The combination of the salinity model, the soil water retention model and the matric potential approach were used to reach this objective. The representation of turfgrass crop relative yield (%) versus a function of soil total water potential f(Ψt) values was shown through a log-normal graph (y = a + mx); the log scale axis “y” (ordinates) defines relative yield Yr, being two the origin ordinate “a” and “m” the slope; the normal decimal scale axis “x” (abscissa) is the function of soil total water potential f(Ψt). Hence, it is possible, using only two experimental points, to define a simple linear relation between a function of soil total water potential and crop relative yield, for a soil matric potential value lower than −20 kPa. This approach was first tested on golf courses (perennial turfgrass fields), but it was further decided to extend it to other annual crop fields, focused on the model generalization. The experimental plots were established, respectively, in Algarve, Alentejo and Oeiras (Portugal) and in the North Negev (Israel). Sprinkler and trickle irrigation systems, under randomized blocks and/or water and salt gradient techniques, were used for water application with a precise irrigation water and salt distribution. Results indicated that there is a high agreement between the experimental and the prediction values (R2 = 0.92). Moreover, the precision of this very simple and easy tool applied to turfgrass fields and other irrigated soils, including their crop yields, under several different sites and climatic conditions, can contribute to its generalization.